SUBSURFACE GEOLOGICAL INTERPRETATION OF THE NORTH SUNDA ASRI BASIN BASED ON SVD ANALYSIS AND GRAVITY ANOMALY MODELING - Hayu Nurfaidah; Imam Setiadi; Muhammad Sarkowi; Ordas Dewanto (BULLETIN OF THE MARINE GEOLOGY, 2023)
The Sunda Asri Basin is dominated by normal faults and has little compressional structure. This basin consists of several depocenters with a thickness of up to 6000 m. Among the geophysical methods, gravity analysis has proven to be effective in determining the bedrock configuration and identifying sedimentary basins. This study aims to analyze sedimentary sub-basin patterns, basement height structures, faults, and bedrock configuration using trend surface analysis of polynomial filters. The analysis of polynomial filter show that a 10th-order anomaly yields optimal results. The high correlation value of 0.990925 provides the suitability of a 10th-order anomaly for qualitative interpretation. Spectral analysis results indicate an average bedrock depth of about 2.75 km within the Sunda Asri Basin. Furthermore, this analysis reveals the presence of 14 sedimentary sub-basin patterns in this area. The gravity modeling results indicate that the top layer has a density value of 2.37 g/cc, which interpreted as Pleistocene Tertiary sediment. The second layer consists of Tertiary-Miocene sediment with a density value of 2.28 g/cc, while the third layer comprises of Pre-Tertiary sedimentary rock at a density of 2.02 g /cc. The bottom layer of the model corresponds to metamorphic bedrock with a density 2.7 g/cc. SVD (Second Vertical Derivative) analysis successfully identified the presence of normal and thrust fault structures